Respuesta :
Answer:
1.8 and -14.7
Step-by-step explanation:
its just to substitute it as t and simplify
Answer:
1.8 and -14.7
Step-by-step explanation:
Given the algebraic expression 1.5t-7.2, to get the value of the expression when t = 6, we will substitute the value of t in the given equation to have;
1.5(6)-7
= 9.0-7.2
= 1.8
Similarly when t = -5, the expression 1.5t-7.2 gives;
1.5(-5)-7.2
= -7.5-7.2
= -14.7
Therefore the expression of the equation at x = 6 is 1.5(6)-7.2 gives 1.8 will at x=-5 gives 1.5(-5)-7.2 which gives -14.7